THE IMPORTANCE OF INTRODUCING STEAM EDUCATIONAL TECHNOLOGY IN CHEMISTRY TEACHING IN SECONDARY SCHOOLS - Shernazarov Iskandar Ergashovich (Bright Mind Publishing, 2025)
The article explains the advantages of using Steam educational technologies for teaching chemistry. At the same time, the importance of integrating disciplines in the organization of lectures, practical and laboratory classes in chemistry, and the formation of students' interest in science based on classes, is expressed.
Keywords: Steam learning technology, Phet Interactive Simulations, chemcollective, PBL problem-based learning.